INOVASI MANAJEMEN TOD (TRANSIT ORIENTED DEVELOPMENT) UNTUK BANDARA DENGAN MENGAMBIL STUDI KASUS : TERMINAL 3 ULTIMATE BANDARA SOEKARNO HATTA (Transit Oriented Development Management Innovation For Airport Case Study : Terminal 3 Ultimate Bandara Soekarno-Hatta) - Aryani Widyakusuma (Fakultas Teknik Universitas Borobudur, 2019)
Transit Oriented Development (TOD) is an approach to developing cities that adoptsa spatial mix of commercial and mixed use residential areas designed to maximizeaccess to public transportation and combine features to encourage transit passengersby maximizing the use of mass transportation such as Busway or BRT, Mass RapidTransportation ( MRT), Light Rail Transit (LRT), and equipped with a pedestrian orbicycle network. Thus the trip will be dominated by using public transportation that isconnected directly to the purpose of the trip. Public transport stops, especially airports,have relatively high densities and are usually equipped with facilities such as arrivalcorridors, boarding lounges, baggage claims, parking lots and more. Soekarno-HattaAirport is one of the largest airports which is the main gateway in Indonesia, whichwas built since 1985. It has applied this TOD concept to its ultimate terminal 3management. Over time, the passenger service capacity which was originally only 22million PAX was inadequate due to current conditions because based on a surveyfrom Airport Council International in 2013 the number of passengers at SoekarnoHatta Airport had reached 52 million PAX. To overcome the density of passengersand air traffic, the development of Soekarno Hatta Airport facilities is very necessaryto improve the quality of service and the convenience of airport service users.Keywords: Transportation, Transit, Development, Commercial, Residential